Validity and reliability of a three-dimensional dental cast simulator for arch dimension measurements - Mahtab Nouri; Sohrab Asefi; Alireza Akbarzadeh Baghban; Amin Aminian; Mohammad Shamsa; Reza Massudi (Wolters Kluwer Medknow Publications, 2014)
Background: The accuracy and reproducibility of measurements in a locally made three dimensional (3D) simulator was assessed and compared with manual caliper measurements. Materials and Methods: A total of 20 casts were scanned by our laser scanner. Software capabilities included dimensional measurements, transformation and rotation of the cast as a whole, separation and rotation of each tooth and clip far. Two orthodontists measured the intercanine width, intermolar width and canine, molar and arch depth on the casts and in 3D simulator. For calculating the reliability coefficient and comparing random and systematic errors between the two methods, intra-class correlation coefficient of reliability (ICC), Dahlberg and paired t-test were used, respectively. The ICC and Dahlberg's formula were also applied to assess intra-examiner and inter-examiner reliability of measurements on the casts and in the simulator (P < 0.05). Results: Canine and molar depth measurements had low reliability on the casts. Reliability between methods for the remaining three variables was 0.87, 0.98 and 0.98 in the maxilla and 0.92, 0.77 and 0.94 in the mandible, respectively. The method error was between 0.31 and 0.48 mm. The mean intra-observer difference were 0.086 and 0.23 mm in the 3D method and caliper. The inter-observer differences were 0.21 and 0.42 mm, respectively. Conclusion: The maximum average absolute difference between the two methods was <0.5 mm, indicating that the new system is indeed clinically acceptable. The examiner reliability was higher in 3D measurements.